Analysis budgeting strategy viewed from consistency of development priority targets for 2023 budget year in Badung District Bali - I Nyoman Tingkes; I Ketut Sirna; Eka Putri Suryantari (Enrichment : Journal of Management, 2023)
The purpose of this study was to analyze the consistency between the budgeting strategy and the priority targets for regional development in Badung Regency for the 2023 Fiscal Year. This research was designed using a concurrently embedded approach. The quantitative data used comes from the 2023 APBD draft document. This data is analyzed by determining the budget allocation ratio. On the other hand, qualitative data, which originates from the results of interviews and observations of focus group discussions between the legislature and the executive during the trial process, is analyzed interactively and continuously between researchers and key informants. The aim is to find patterns of relationship between budgeting strategies and regional development priority targets. The results of the study found that (a) there was an inconsistency between the budgeting strategy and the priority targets for regional development, (b) the cause of the inconsistency was the implementation of the provisions of Article 181 of the Regulation of the Minister of Home Affairs Number 86, 2017 co ncerning Evaluation and Control of Regional Development, which was not optimal. Based on the results of this research, it can be suggested to the regents, governors and minister of home affairs to be more optimal in evaluating and controlling regional development.